Neurocognitive dysfunction in hematopoietic cell transplant recipients: expert review from the late effects and Quality of Life Working Committee of the CIBMTR and complications and Quality of Life Working Party of the EBMT. (May 2018) - Buchbinder, David; Kelly, Debra; Duarte, Rafael; Auletta, Jeffery; Bhatt, Neel; Byrne, Michael; DeFilipp, Zachariah; Gabriel, Melissa; Mahindra, Anuj; Norkin, Maxim; Schoemans, Helene; Shah, Ami; et al.
Abstract Hematopoietic cell transplantation (HCT) is a potentially curative treatment for children and adults with malignant and non-malignant diseases. Despite increasing survival rates, long-term morbidity following HCT is substantial. Neurocognitive dysfunction is a serious cause of morbidity, yet little is known about neurocognitive dysfunction following HCT. To address this gap, collaborative efforts of the Center for International Blood and Marrow Transplant Research and the European Society for Blood and Marrow Transplantation undertook an expert review of neurocognitive dysfunction following HCT. In this review, we define what constitutes neurocognitive dysfunction, characterize its risk factors and sequelae, describe tools and methods to assess neurocognitive function in HCT recipients, and discuss possible interventions for HCT patients with this condition. This review aims to help clinicians understand the scope of this health-related problem, highlight its impact on well-being of survivors, and to help determine factors that may improve identification of patients at risk for declines in cognitive functioning after HCT. In particular, we review strategies for preventing and treating neurocognitive dysfunction in HCT patients. Lastly, we highlight the need for well-designed studies to develop and test interventions aimed at preventing and improving neurocognitive dysfunction and its sequelae following HCT.